Development of reed-based cellulose aerogel: a sustainable solution for crude oil spill clean-up - Huong Le Thi Thanh; An Tran Nguyen Minh; Hoang Tran Huu (Royal Society Open Science)
This study focused on fabricating a cellulose aerogel for oil spill clean-up, using common reed (Phragmites australis) as the cellulose source. The process involved isolating cellulose from reed via traditional Kraft pulping, considering the effects of key factors on the isolated cellulose content. After a two-stage HP bleaching sequence, the highest cellulose content achieved was 27.2%, with 80% ISO brightness and 1% ash content under mild Kraft pulping conditions of 30% sulfidity, 20% active alkali (AA), sustained cooking at 165°C for 3 h, and a liquor-to-reed ratio of 8 : 1. Subsequently, reed-based cellulose aerogel was fabricated via a freeze-drying method using an eco-friendly NaOH/poly(ethylene glycol) aqueous solvent system, which was then modified with methyltrimethoxysilane. The resulting aerogel exhibited remarkable characteristics, including a low density of 0.04 g cm−3, high porosity of 96%, high hydrophobicity with a water contact angle (WAC) of 141°, and a superior crude oil adsorption capacity of 35 g g−1. Comprehensive characterizations of the fabricated materials, including scanning electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis/differential scanning calorimetry, and WAC measurements, were evaluated. This interdisciplinary study explores the commercial promise of reed-based cellulose aerogel as a sustainable solution for oil spill clean-up efforts.